Peningkatan Kemampuan Membaca Puisi pada Siswa Kelas VII-B UPT SMP Negeri 1 Tellu Limpoe Kabupaten Sidenreng Rappang dengan Metode Demonstrasi - Asia (Kilau Publishing, 2024)
The choice of demonstration method is a challenge for the teacher. The teacher will be a model in front of the class, thus the teacher will try to improve his/her quality. This research aims to determine the effect of the demonstration method in improving poetry reading skills in class VII-B UPT SMP Negeri 1 Tellu Limpoe Sidenreng Rappang Regency which has an impact on achievement, understanding and mastery of Indonesian language subjects. This research was conducted in class VII-B UPT SMP Negeri 1 Tellu Limpoe Sidenreng Rappang Regency with the number of students in the research class was 28 students. The research method used in this research is descriptive statistical analysis method by collecting pre-cycle to cycle II results. The results explained that Indonesian language learning activities using the demonstration method were effective in improving students' ability to read poetry. The demonstration method as an approach is very helpful in facilitating students' understanding of poetry reading material in the context of Indonesian language learning. However, learning by using the demonstration method requires careful teaching preparation and effective time and class management. This is necessary to achieve optimal learning outcomes in every activity in the classroom.